Mechanical Design Verification of CHASNUPP Bottom Nozzle - Khan, Waseem; Anwer, Muhammad Arslan; Siddiqui, Ashfaq Ahmad (The Nucleus, 2023)
The bottom nozzle is a critical component of the fuel assembly of 340 MWe PWR Nuclear Power Plant at Chashma site (CHASNUPP). It bears axial loads during fabrication, handling, transportation, and reactor operation. The perforated plate, containing flow-holes of complex orientation, is the main critical load bearing and supporting component of the bottom nozzle. Therefore, mechanical strength and stresses of the bottom nozzle need to be analyzed and tested under limiting load conditions, i.e., transportation load 6g. The present study is an attempt to develop the finite element (FE) methodology in order to assess the structural integrity and determine the maximum stress concentration area of the bottom nozzle at applied limiting load of 6g, at standard temperature and pressure (STP). The FE model of the bottom nozzle was produced by solid element (C3D8R) and solved by the static linear analysis using computer code ABAQUS/CAE 6.10-1. Final results acquired from the FE analysis are compared with the mechanical compression test results for mechanical design verification. The values of maximum stress calculated through FE analysis are much comparable with the stress values obtained from each strain gauge at similar locations, which confirmed the accuracy of the FE methodology. The value of the max. von-mises stress (Seqv.), obtained by the FE analysis, and max. value of the stress obtained through test, under applied load of 6g, are less than the design stress limit (yield strength) of bottom nozzle material, SS-321, thereby verifying its structural integrity as well as satisfying its mechanical design criteria under limiting load of 6 g.